Common data elements for unruptured intracranial aneurysm and subarachnoid hemorrhage clinical research: recommendations from the working group on long-term therapies - Wong, George; Daly, Janis J.; Rhoney, Denise H.; Broderick, Joseph; Ogilvy, Christopher; Roos, Y. B.; Siddiqui, Adnan; Torner, James; Etminan, Nima; Hackenberg, Katharina (Neurocritical care, 2019)
The goal for the long-term therapies (LTT) working group (WG) of the Unruptured Intracranial Aneurysm (UIA) and Subarachnoid Hemorrhage (SAH) common data elements (CDEs) was to develop a comprehensive set of CDEs, data definitions, case report forms, and guidelines for use in UIA and SAH LTT clinical research, as part of a new joint effort between the National Institute of Neurological Disorders and Stroke (NINDS) and the National Library of Medicine of the US National Institutes of Health. These UIA and SAH CDEs will join other neurological disease-specific CDEs already developed and available for use by research investigators. The eight LTT WG members comprised international UIA, and SAH experts reviewed existing NINDS CDEs and instruments, created new elements when needed, and provided recommendations for future LTT clinical research. The recommendations were compiled, internally reviewed by the all UIA and SAH WGs and steering committee members. The NINDS CDE team also reviewed the final version before posting the SAH Version 1.0 CDE recommendations on the NINDS CDE website. The NINDS UIA and SAH LTT CDEs and supporting documents are publicly available on the NINDS CDE (https://www.commondataelements.ninds.nih.gov/#page=Default) and NIH Repository (https://cde.nlm.nih.gov/home) websites. The subcommittee members discussed and reviewed various parameters, outcomes, and endpoints in UIA and SAH LTT studies. The following meetings with WG members, the LTT WG’s recommendations are incorporated into the disease/injury-related events, assessments and examinations, and treatment/intervention data domains.Noting gaps in the literature regarding medication and rehabilitation parameters in UIA and SAH clinical studies, the current CDE recommendations aim to arouse interest to explore the impact of medication and rehabilitation treatments and therapies and encourage the convergence of LTT clinical study parameters to develop a harmonized standard.
Gesehen am 02.10.2019